Development of Photochemical Activity in Relation to Pigment and Membrane Protein Accumulation in Chloroplasts of Barley and Its Virescens Mutant - Kyle, David J. (1982)
The development of photochemical activity in relation to pigment and membrane protein accumulation in chloroplasts of greening wild-type barley (Hordeum vulgare L. cv. Gateway) and its virescens mutant were studied. The rate of chlorophyll accumulation per plastid was faster in the wild-type than in the mutant seedlings upon illumination after 6 days of etiolation, but was not different after 8 days. Although the protein content per plastid did not vary during greening, there was a change in the sodium dodecyl sulfate-polyacrylamide gel polypeptide profiles. High molecular weight proteins of 96,000 and 66,000 decreased whereas those at 34,000, 27,000 and 22,000 increased in relative quantity as a function of greening. The fully greened mutant seedlings were not deficient in the light-harvesting chlorophyll protein complex (LHC) or the reaction centers of photosystem I and photosystem II. Photosystem I-associated photochemical activities appeared within the first hour of plastid development and photosystem II associated activities and O(2) evolution within the next 6 hours. In all cases, the developmental rates per unit protein were slower in the mutant following 6 days of etiolation, but no differences between the two genotypes could be seen after 8 days due to a decrease in the developmental rate of the wild-type chloroplasts. An increase in photosynthetic unit size associated with plastid morphogenesis was faster in the wild-type seedlings after 6 days, but again the difference was negligible after 8 days. It was concluded that no single measured photochemical parameter is affected by this mutation, but rather, all aspects of chloroplast development are affected similarly by an overall reduction in the rate of chloroplast morphogenesis. This mutant, therefore, undergoes the normal pattern of proplastid to chloroplast development, but at a markedly reduced rate.